Plant Regeneration Through Direct Somatic Embryogenesis from Leaf Explants of Paraphalaenopsis Labukensis P. S. Shim. (November 2019) - Garvita, R.Vitri; Sahromi,
Abstract: Paraphalaenopsis is a small genus of the tribe Vandeae, the genus comprises 4 species: Paraphalaenopsis denevei, Paraphalaenopsis laycockii, Paraphalaenopsis labukensis and Paraphalaenopsis serpentilingua. All are known endemic to Borneo, and also rare due to over exploitation, therefore requires rescue efforts. In vitro culture is one of effort that can be done to regenerate a large number of seedlings and to ex situ conservation. Optimal growth and morphogenesis of tissues may vary for different plants according to their nutritional requirement. Auxin (NAA) is an essential factor for root growth in tissue culture work. Activated charcoal is often used in tissue culture to improve cell growth and development. This research was conducted to find out the in vitro growth effect from leaf explants of P. labukensis with plant growth regulators (NAA) and activated charcoal on ½ MS medium as basal medium. The treatment with NAA 2 ppm and 1 g/l activated charcoal showed the highest percentage of life (50 %) and percentage of leaf (57.1 %). The largest percentage of roots showed in 2 g/l activated charcoal (35.7 %). The death of leaf explants P. labukensis was caused by browning. The phenolic compound which accumulated during wounding is causing browning.